The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.11130/jei.2017.32.3.531
|View full text |Cite
|
Sign up to set email alerts
|

International Trade and Employment: A Quantile Regression Approach

Abstract: Existing studies on the relationship between international trade and manufacturing employment often use a mean regression approach and focus mainly on developed countries. Few studies have applied a quantile regression approach to examine this relationship in developing countries. To fill the gap, this study considers, for the first time, the impact of rising international trade on employment in a developing country, Vietnam. Using an unbalanced panel dataset for the 2010~2015 period, we find a positive linkag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…ECM results revealed a positive relationship between exports and female employment. Similarly, Ha and Tran (2017), investigated the relationship between the number of employees of the firms operating in manufacturing and manufacturing via the panel data method for the period 2010-2015. The results showed that exports affected employment positively.…”
Section: The Summary Of the Literaturementioning
confidence: 99%
“…ECM results revealed a positive relationship between exports and female employment. Similarly, Ha and Tran (2017), investigated the relationship between the number of employees of the firms operating in manufacturing and manufacturing via the panel data method for the period 2010-2015. The results showed that exports affected employment positively.…”
Section: The Summary Of the Literaturementioning
confidence: 99%
“…The quantile estimator also provides a richer characterisation of the data, allowing us to study the effect of the quality of public governance on the entire distribution of household welfare, not merely its conditional mean (Koenker & Hallock, ). In addition, a quantile regression estimator is more robust to non‐normal errors and outliers, whereas a linear regression estimator can suffer from inefficiency if the errors are highly abnormal (Ha & Tran, ; Koenker, ).…”
Section: Methodsmentioning
confidence: 99%
“…Recent studies include for example, Djankov and Ramalho (), Aydiner‐Avsar and Onaran (), Hollweg et al . (), Gozgor (), Ha and Tran (), Fugazza et al . ().…”
Section: Empirical Modelmentioning
confidence: 99%
“…Many studies have been performed on the macroeconomic determinants of employment, specifically in developing countries. Recent studies include for example, Djankov and Ramalho (2009), Aydiner-Avsar and Onaran (2010), Hollweg et al (2016), Gozgor (2017), Ha and Tran (2017), Fugazza et al (2017). To examine the impact of AfT on employment in recipient countries, we draw on many insights from these studies and postulate the following model:…”
Section: Empirical Modelmentioning
confidence: 99%
See 1 more Smart Citation